Low-temperature-resistant anti-crack concrete and preparation method thereof

By using the formula of modified polyurethane and modified hydrotalcite in concrete, the problem of easy destruction of concrete in high-altitude western regions under extreme climatic conditions is solved, the durability and crack resistance of concrete are improved, and its flame retardant and ultraviolet resistance are enhanced.

CN119841578AActive Publication Date: 2025-04-18SHANDONG EXPRESSWAY QILU CONSTR GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510097606.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-18
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

In the high-altitude areas in the western region, concrete is prone to freeze-thaw damage under extreme climatic conditions, resulting in significantly shortening its durability and service life. Polyurethane concrete ages under ultraviolet rays, affecting durability.

Method used

A low-temperature resistant and crack-resistant concrete is used, and its formulation includes 95-105 parts of ore and 3-9 parts of modified polyurethane. The modified polyurethane consists of 4-8 parts of polyurethane and 1.3-1.7 parts of modified hydrotalcite. The modified hydrotalcite consists of 2.1-2.9 parts of hydrotalcite and 0.4-0.8 parts of vinyl prepolymer. The vinyl prepolymer improves its hydrophilicity and dispersion through specific composition and treatment methods.

Benefits of technology

The layered structure of modified hydrotalcite can absorb ultraviolet rays, reduce its damage to polyurethane, improve the anti-aging properties of polyurethane, and thus improve the durability and crack resistance of concrete. At the same time, the addition of modified phosphides improves flame retardant properties and UV resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of concrete, and particularly discloses low-temperature-resistant anti-crack concrete and a preparation method thereof. The low-temperature-resistant anti-crack concrete is prepared from the following raw materials in parts by mass: 95 to 105 parts of mineral aggregate and 3 to 9 parts of modified polyurethane, the modified polyurethane is prepared from the following raw materials in parts by mass: 4 to 8 parts of polyurethane and 1.3 to 1.7 parts of modified hydrotalcite; the modified hydrotalcite is prepared from the following raw materials in parts by mass: 2.1 to 2.9 parts of hydrotalcite and 0.4 to 0.8 part of vinyl prepolymer; the preparation method comprises the following steps: weighing 95-105 parts of mineral aggregate, placing the mineral aggregate at 20-30 DEG C, and uniformly mixing and stirring the mineral aggregate with 3-9 parts of modified polyurethane. The low-temperature-resistant anti-crack concrete has the advantage that the defect that the durability of the low-temperature-resistant anti-crack concrete is still insufficient can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete technology, and more specifically, to a low temperature resistant and crack resistant concrete and a preparation method thereof. Background Art

[0002] As a hard building material, concrete is made of cementitious materials (usually Portland cement, also known as ordinary cement or silicate cement) and mineral aggregates (such as washed sand and gravel or crushed stone) mixed with enough water to solidify and bind the cement. With the healthy urbanization process and the continuous improvement of building functional requirements, the shortcomings of the original concrete materials in terms of performance and applicability have been exposed. The high-altitude areas in western China have large temperature differences between day and night, severe cold and dryness, strong solar radiation, and deep permafrost. The extreme climate causes severe freeze-thaw damage to concrete, greatly reducing the durability of concrete. After 5 to 10 years of use, concrete building materials on the Qinghai-Tibet Plateau will have problems such as powdering of the concrete surface, exposed aggregates, and breaking when tapped lightly. The service life of concrete structures is significantly shortened and poses safety hazards. Therefore, improving the low-temperature resistance and crack resistance of concrete in the western high-altitude cold areas is crucial to extending its service life.

[0003] Polyurethane concrete is widely used in building materials because of its excellent low-temperature resistance, good flexibility at low temperatures, and not easy to crack after repeated freezing and thawing. However, since polyurethane itself is not resistant to ultraviolet rays, when polyurethane is exposed to ultraviolet rays for a long time, it will cause aging of polyurethane, thus affecting the durability of concrete. Summary of the invention

[0004] In order to improve the defect that the durability of low-temperature resistant and crack-resistant concrete is still insufficient, the present application provides a low-temperature resistant and crack-resistant concrete and a preparation method thereof.

[0005] In the first aspect, the present application provides a low temperature resistant and crack resistant concrete, which adopts the following technical solution: A low temperature resistant and crack resistant concrete, comprising the following raw materials by weight: 95-105 parts of mineral material and 3-9 parts of modified polyurethane; The modified polyurethane comprises the following raw materials in parts by weight: 4-8 parts of polyurethane and 1.3-1.7 parts of modified hydrotalcite; The modified hydrotalcite comprises the following raw materials in parts by weight: 2.1-2.9 parts of hydrotalcite and 0.4-0.8 parts of vinyl prepolymer.

[0006] Since polyurethane contains urethane bonds and ether bonds, these bonds are easily broken under ultraviolet rays, causing material degradation. Ultraviolet rays can excite oxygen atoms in polyurethane to produce free radicals, thereby triggering a chain oxidation reaction. This photooxidation will destroy the long-chain molecular structure of polyurethane and reduce its physical properties. Hydrotalcite has a layered structure, consisting of two layers of positively charged metal hydroxide layers and a layer of negatively charged interlayer anions. Its interlayer anions can absorb ultraviolet rays, thereby reducing the damage of ultraviolet rays to polyurethane. The anti-aging properties of polyurethane are also improved, thereby improving the durability of concrete.

[0007] Since hydrotalcite, as an inorganic substance, has strong hydrophilicity, the dispersion of hydrotalcite is poor when mixed with polyurethane. Vinyl prepolymer has unique hydrophilicity, which enables the vinyl prepolymer to be adsorbed on the surface of hydrotalcite particles to form a coating layer, thereby reducing the direct contact between hydrotalcite particles and reducing the possibility of hydrotalcite agglomeration.

[0008] Preferably, the vinyl prepolymer comprises the following raw materials in parts by mass: 1.5-3.5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 1-1.6 parts of acrylic acid, 0.5-0.9 parts of sodium p-styrenesulfonate, 0.5-1.5 parts of dimethyldiallylammonium chloride, 3-3.8 parts of acrylamide, 0.02-0.08 parts of initiator and 0.15-0.21 parts of modified phosphide.

[0009] Since 2-acrylamido-2-methylpropanesulfonic acid contains sulfonic acid groups, the sulfonic acid groups can interact with the metal ions of hydrotalcite. Acrylic acid contains carboxyl groups and can also interact with the surface of hydrotalcite. Sodium p-styrenesulfonate contains benzene rings and sulfonic acid groups. The benzene ring provides hydrophobic effect and the sulfonic acid group provides hydrophilic effect, which helps to regulate the interfacial interaction between the prepolymer and the hydrotalcite. Dimethyldiallylammonium chloride is a cationic monomer that can neutralize the negative charge on the surface of the hydrotalcite, reduce the electrostatic attraction between the particles, and thus improve the dispersibility. The macromolecular chain formed by the polymerization of acrylamide can provide steric hindrance, thereby reducing the agglomeration between the hydrotalcite particles.

[0010] Preferably, the preparation method of the vinyl prepolymer is as follows: 1.5-3.5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 1-1.6 parts of acrylic acid, 0.5-0.9 parts of sodium p-styrene sulfonate and 0.15-0.21 parts of modified phosphide are weighed and added into a beaker, 15-25 ml of deionized water is added for dissolution, the pH value is adjusted, then 0.5-1.5 parts of dimethyldiallylammonium chloride, 3-3.8 parts of acrylamide and 0.02-0.08 parts of initiator are added, stirred evenly to completely dissolve all monomers, nitrogen is passed through for 5-15 minutes, and then placed in a constant temperature water bath at 45-55° C., reacted for 4-8 hours, washed with anhydrous ethanol and then sheared and granulated.

[0011] Preferably, the modified phosphide comprises the following raw materials: 1-3 g of triaminomethylphosphine oxide, 1-2 g of hexachlorocyclotriphosphazene, 0.5-1.5 g of melamine, 35-65 ml of N,N-dimethylformamide, and 2-8 ml of triethylamine.

[0012] Since concrete is mainly composed of inorganic materials such as cement, sand, gravel and water, these materials do not contain organic combustible substances under normal conditions, so they are not easy to burn and have good flame retardant properties. Polyurethane contains a large amount of carbon and hydrogen atoms. During the combustion process, these carbon and hydrogen atoms easily react chemically with oxygen, thereby releasing heat and combustible gases, accelerating the combustion process, and thus causing the overall flame retardant properties of concrete to decrease.

[0013] Triaminomethylphosphine oxide contains phosphorus, which can form phosphoric acid or its derivatives when burned. These substances can act as acid sources to promote carbonization, forming a carbon layer to isolate oxygen and heat, thereby preventing continued combustion. Since hexachlorocyclotriphosphazene and melamine can form a polyphosphazene structure, the polyphosphazene structure formed by hexachlorocyclotriphosphazene and melamine is rich in P and N elements, which can also improve the flame retardant properties of triaminomethylphosphine oxide. Hexachlorocyclotriphosphazene contains multiple chlorine atoms and phosphorus atoms, which can absorb the energy of ultraviolet rays. Melamine itself has a certain ultraviolet light stabilization effect. Therefore, the addition of modified phosphides can not only improve the anti-ultraviolet properties of modified polyurethane, but also improve the flame retardant properties of polyurethane.

[0014] Preferably, the preparation method of the modified phosphide is as follows: 1-3g of triaminomethylphosphine oxide is weighed and dispersed in 15-25mlN,N-dimethylformamide, and placed in an ice bath for stirring; 1-2g of hexachlorocyclotriphosphazene is weighed and added to a beaker, and ultrasonically dispersed with 5-15ml N,N-dimethylformamide, and then added dropwise to the triaminomethylphosphine oxide dispersion; after the dropwise addition is completed, the reaction is continued for 25-35min; 0.5-1.5g of melamine is weighed and added to a beaker, and ultrasonically dispersed with 15-25ml N,N-dimethylformamide, and then added dropwise to the above dispersion; 2-8ml of triethylamine is continued to be added dropwise to the above dispersion; after the dropwise addition is completed, the reaction is continued for 25-35min; the uniformly stirred dispersion is poured into a high-pressure reactor and reacted at 100-140°C for 24-28h, and then centrifuged at a high speed; the product is then dried at 75-85°C for 2-8h and ground into powder.

[0015] Preferably, the preparation method of the modified hydrotalcite is as follows: 2.1-2.9 parts of hydrotalcite and 0.4-0.8 parts of vinyl prepolymer are weighed and mixed evenly, dried in an oven at 75-85° C. for 6-10 hours, extruded and granulated on an extruder at 210-250° C., and injection molded.

[0016] Preferably, the preparation method of the modified polyurethane is as follows: 1.3-1.7 parts of modified hydrotalcite are added to 4-8 parts of polyurethane and stirred evenly, and then placed in a high-speed shearing machine for shearing treatment.

[0017] In a second aspect, the present application provides a method for preparing low temperature resistant and crack resistant concrete, which adopts the following technical solution: A method for preparing low-temperature resistant and crack resistant concrete comprises the following steps: weighing 95-105 parts of mineral materials, placing them at 20-30 DEG C, and mixing them with 3-9 parts of modified polyurethane and stirring them uniformly.

[0018] In summary, this application has the following beneficial effects: 1. Since polyurethane contains urethane bonds and ether bonds, these bonds are easily broken under ultraviolet rays, resulting in material degradation. Ultraviolet rays can excite oxygen atoms in polyurethane to produce free radicals, thereby initiating a chain oxidation reaction. This photooxidation will destroy the long-chain molecular structure of polyurethane and reduce its physical properties. Hydrotalcite has a layered structure consisting of two layers of positively charged metal hydroxide layers and a layer of negatively charged interlayer anions. Its interlayer anions can absorb ultraviolet rays, thereby reducing the damage of ultraviolet rays to polyurethane. The anti-aging properties of polyurethane are also improved, thereby improving the durability of concrete.

[0019] Since hydrotalcite, as an inorganic substance, has strong hydrophilicity, the dispersion of hydrotalcite is poor when mixed with polyurethane. Vinyl prepolymer has unique hydrophilicity, which enables the vinyl prepolymer to be adsorbed on the surface of hydrotalcite particles to form a coating layer, thereby reducing the direct contact between hydrotalcite particles and reducing the possibility of hydrotalcite agglomeration.

[0020] 2. Since 2-acrylamido-2-methylpropanesulfonic acid contains sulfonic acid groups, the sulfonic acid groups can interact with the metal ions of hydrotalcite. Acrylic acid contains carboxyl groups and can also interact with the surface of hydrotalcite. Sodium p-styrene sulfonate contains benzene rings and sulfonic acid groups. The benzene ring provides hydrophobic effect and the sulfonic acid group provides hydrophilic effect, which helps to regulate the interfacial interaction between the prepolymer and the hydrotalcite. Dimethyldiallylammonium chloride is a cationic monomer that can neutralize the negative charge on the surface of the hydrotalcite, reduce the electrostatic attraction between particles, and thus improve the dispersibility. The macromolecular chain formed by polymerization of acrylamide can provide steric hindrance, thereby reducing the agglomeration between hydrotalcite particles.

[0021] 3. Since concrete is mainly composed of inorganic materials such as cement, sand, gravel and water, these materials do not contain organic combustible substances under normal conditions, so they are not easy to burn and have good flame retardant properties. Polyurethane contains a large amount of carbon and hydrogen atoms. During the combustion process, these carbon and hydrogen atoms easily react chemically with oxygen, thereby releasing heat and combustible gases, accelerating the combustion process, and thus causing the overall flame retardant properties of concrete to decrease.

[0022] Triaminomethylphosphine oxide contains phosphorus, which can form phosphoric acid or its derivatives when burned. These substances can act as acid sources to promote carbonization, forming a carbon layer to isolate oxygen and heat, thereby preventing continued combustion. Since hexachlorocyclotriphosphazene and melamine can form a polyphosphazene structure, the polyphosphazene structure formed by hexachlorocyclotriphosphazene and melamine is rich in P and N elements, which can also improve the flame retardant properties of triaminomethylphosphine oxide. Hexachlorocyclotriphosphazene contains multiple chlorine atoms and phosphorus atoms, which can absorb the energy of ultraviolet rays. Melamine itself has a certain ultraviolet light stabilization effect. Therefore, the addition of modified phosphides can not only improve the anti-ultraviolet properties of modified polyurethane, but also improve the flame retardant properties of polyurethane. DETAILED DESCRIPTION

[0023] The present application is further described in detail below in conjunction with Examples 1-14 and Comparative Examples 1-3.

[0024] raw material: Minerals Suzhou Gangsong Building Materials Co., Ltd.; Polyurethane Shenyang Elex Chemical Co., Ltd.; Hydrotalcite CAS: 12304-65-3; 2-Acrylamido-2-methylpropanesulfonic acid CAS: 15214-89-8; Acrylic acid CAS: 79-10-7; Sodium p-styrene sulfonate CAS: 2695-37-6; Deionized water CAS: 7732-18-5; Sodium hydroxide CAS: 1310-73-2; Dimethyldiallylammonium chloride CAS: 7398-69-8; Propylene Amide CAS: 79-06-1; ammonium persulfate CAS: 7727-54-0; sodium bisulfite CAS: 7631-90-5; nitrogen CAS: 7727-37-9; anhydrous ethanol CAS: 64-17-5; triaminomethylphosphine oxide CAS: 545-55-1; hexachlorocyclotriphosphazene CAS: 940-71-6; melamine CAS: 108-78-1; N,N-dimethylformamide CAS: 68-12-2; triethylamine CAS: 121-44-8.

[0025] Example Example 1 A low-temperature resistant and crack-resistant concrete comprises the following raw materials: 100 g of mineral material and 6 g of modified polyurethane.

[0026] Specifically, the preparation method of low temperature resistant and crack resistant concrete comprises the following steps: S1: Weigh 2 g of triaminomethylphosphine oxide and disperse it in 20 ml of N, N-dimethylformamide, and place it in an ice bath for stirring. Weigh 1.5 g of hexachlorocyclotriphosphazene and add it to a beaker. After ultrasonic dispersion with 10 ml of N, N-dimethylformamide, add it dropwise to the triaminomethylphosphine oxide dispersion. After the addition is complete, continue the reaction for 20 min. S2: Weigh 1 g of melamine into a beaker, disperse it with 20 ml of N,N-dimethylformamide by ultrasonic, and then add it dropwise into the dispersion in S1; S3: Weigh 5 ml of triethylamine and continue to add it dropwise to the dispersion in S2. After the addition is complete, continue to react for 30 minutes. Pour the evenly stirred dispersion into a high-pressure reactor and react at 120°C for 26 hours. Then, centrifuge at a high speed. Then, dry the product in an oven at 80°C for 5 hours and grind it into powder to obtain the modified phosphide. S4: weigh 2.5g of 2-acrylamido-2-methylpropanesulfonic acid, 1.3g of acrylic acid, 0.7g of sodium p-styrenesulfonate and 0.18g of modified phosphide and add them into a beaker, add 20ml of deionized water to dissolve, add 30% sodium hydroxide aqueous solution dropwise until the solution pH = 7, then add 1g of dimethyldiallylammonium chloride, 3.4g of acrylamide and 0.05g of initiator, stir evenly to completely dissolve all monomers, pass nitrogen for 10min, seal with plastic wrap, put into a constant temperature water bath at 50°C, react for 6h, wash with anhydrous ethanol and then shear and granulate to obtain a vinyl prepolymer; Wherein, the initiator includes 0.03g ammonium persulfate and 0.02g sodium bisulfite; S5: Weigh 2.5 g of hydrotalcite and 0.6 g of vinyl prepolymer, mix them evenly, dry them in an oven at 80° C. for 8 h, extrude them into granules on an extruder at 230° C., and perform injection molding to obtain modified hydrotalcite; S6: adding 1.5 g of modified hydrotalcite to 6 g of polyurethane and stirring evenly, and then placing the mixture into a high-speed shearing machine for shearing to obtain modified polyurethane; S7: Weigh 100g of mineral material, place it at 25°C, and mix it with 6g of modified polyurethane in a conventional manner to obtain low-temperature resistant and crack-resistant concrete.

[0027] Example 2-3 The difference from Example 1 is that the addition amount of each component of the low temperature resistant and crack resistant concrete is different, as shown in Table 1.

[0028] Table 1 Addition amount of each component of low temperature resistant and crack resistant concrete in Examples 1-3 (g)

[0029] Example 4 The difference from Example 1 is that the modified hydrotalcite is replaced by an equal amount of carbon black.

[0030] Example 5 The difference from Example 1 is that the modified phosphide is replaced by an equal amount of triaminomethylphosphine oxide.

[0031] Example 6 The difference from Example 1 is that no modified phosphide is added.

[0032] Embodiment 7-8 The difference from Example 1 is that the addition amount of each component of the modified phosphide is different, as shown in Table 2.

[0033] Table 2 Addition amount of each component of modified phosphide in Example 1 and Examples 7-8

[0034] Examples 9-10 The difference from Example 1 is that the added amounts of the various components of the vinyl prepolymer are different, as shown in Table 3.

[0035] Table 3 Addition amount of each component of vinyl prepolymer in Example 1 and Examples 9-10

[0036] Examples 11-12 The difference from Example 1 is that the addition amount of each component of the modified hydrotalcite is different, as shown in Table 4.

[0037] Table 4 Addition amount of each component of modified hydrotalcite in Example 1 and Examples 11-12 (g)

[0038] Examples 13-14 The difference from Example 1 is that the added amounts of the various components of the modified polyurethane are different, as shown in Table 5.

[0039] Table 5 Addition amount of each component of modified polyurethane in Example 1 and Examples 13-14 (g)

[0040] Comparative Example Comparative Example 1 The difference from Example 1 is that no vinyl prepolymer is added.

[0041] Comparative Example 2 The difference from Example 1 is that no modified hydrotalcite is added.

[0042] Comparative Example 3 The difference from Example 1 is that no modified polyurethane is added.

[0043] Performance testing Detection Methods 1. Durability test Three samples were taken from Examples 1-14 and Comparative Examples 1-3, respectively, and the electric flux, chloride ion diffusion coefficient and carbonation depth of the concrete were measured according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The sample size was 100mm×100mm×100mm, and the durability test was carried out.

[0044] The test data is shown in Table 6.

[0045] Table 6 Durability test table of Examples 1-14 and Comparative Examples 1-3

[0046] Combining Example 1 and Comparative Example 1 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of Comparative Example 1 after 28 days of sample curing both increase significantly, which indicates that the addition of vinyl prepolymer can effectively improve the durability of low-temperature resistant and crack-resistant concrete.

[0047] The reason is that vinyl prepolymer has unique hydrophilicity, which enables vinyl prepolymer to be adsorbed on the surface of hydrotalcite particles to form a coating layer, thereby reducing the direct contact between hydrotalcite particles and reducing the possibility of hydrotalcite agglomeration. Therefore, hydrotalcite and polyurethane can be better mixed, thereby improving the anti-aging properties of polyurethane and thus improving the durability of concrete.

[0048] Combining Example 1 and Comparative Example 2 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of Comparative Example 2 after 28 days of sample curing also increased significantly, which shows that adding modified hydrotalcite can effectively improve the durability of low-temperature resistant and crack-resistant concrete.

[0049] The reason is that the modified hydrotalcite has a layered structure, consisting of two layers of positively charged metal hydroxide layers and a layer of negatively charged interlayer anions. The interlayer anions can absorb ultraviolet rays, thereby reducing the damage of ultraviolet rays to polyurethane. The anti-aging properties of polyurethane are also improved, thereby improving the durability of concrete.

[0050] Combining Example 1 and Comparative Example 3 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of Comparative Example 3 after 28 days of sample curing also increased significantly, which shows that, relative to conventional concrete, adding modified polyurethane can effectively improve the durability of low-temperature resistant and crack-resistant concrete.

[0051] Combining Example 1 and Example 2-3 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the samples of Example 2 and Example 3 increased after 28 days of sample curing, which shows that the addition amount of each component of the low-temperature resistant and crack-resistant concrete affects the durability of the low-temperature resistant and crack-resistant concrete to a certain extent.

[0052] Combining Example 1 and Example 4 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the sample in Example 4 increased significantly after 28 days of sample curing, which shows that, relative to the addition of carbon black, the addition of modified hydrotalcite can effectively improve the durability of low-temperature resistant and crack-resistant concrete.

[0053] Combining Example 1 and Example 5 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the sample in Example 5 increased significantly after 28 days of sample curing, which shows that, relative to the addition of triaminomethylphosphine oxide alone, the addition of modified phosphide can effectively improve the durability of low-temperature resistant and crack-resistant concrete.

[0054] Combining Example 1 and Example 6 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the sample in Example 6 increased significantly after 28 days of sample curing, which shows that, relative to not adding modified phosphides, adding modified phosphides can effectively improve the durability of low-temperature resistant and crack-resistant concrete.

[0055] Combining Example 1 and Examples 7-8 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the samples of Examples 7 and 8 increased slightly after 28 days of sample curing, which shows that the addition amount of each component of the modified phosphide affects the durability of the low-temperature resistant and crack-resistant concrete.

[0056] Combining Example 1 with Examples 9-10 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the samples of Examples 9 and 10 increased slightly after 28 days of curing, which shows that the addition amount of each component of the vinyl prepolymer affects the durability of the low-temperature resistant and crack-resistant concrete.

[0057] Combining Example 1 and Examples 11-12 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the samples of Examples 11 and 12 increased slightly after 28 days of sample curing, which shows that the addition amount of each component of the modified hydrotalcite affects the durability of the low-temperature resistant and crack-resistant concrete.

[0058] Combining Example 1 and Examples 13-14 and Table 6, it can be seen that, relative to Example 1, the electric flux and chloride ion diffusion coefficient of the samples of Example 13 and Example 14 increased slightly after 28 days of sample curing, which shows that the addition amount of each component of the modified polyurethane affects the durability of the low-temperature resistant and crack-resistant concrete.

[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low temperature resistant and crack resistant concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 95-105 parts of mineral material and 3-9 parts of modified polyurethane; The modified polyurethane comprises the following raw materials in parts by weight: 4-8 parts of polyurethane and 1.3-1.7 parts of modified hydrotalcite; The modified hydrotalcite comprises the following raw materials in parts by weight: 2.1-2.9 parts of hydrotalcite and 0.4-0.8 parts of vinyl prepolymer.

2. The low temperature resistant and crack resistant concrete according to claim 1, characterized in that: The vinyl prepolymer comprises the following raw materials in parts by weight: 1.5-3.5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 1-1.6 parts of acrylic acid, 0.5-0.9 parts of sodium p-styrenesulfonate, 0.5-1.5 parts of dimethyldiallylammonium chloride, 3-3.8 parts of acrylamide, 0.02-0.08 parts of initiator and 0.15-0.21 parts of modified phosphide.

3. The low temperature resistant and crack resistant concrete according to claim 2, characterized in that: The preparation method of the vinyl prepolymer comprises the following steps: weighing 1.5-3.5 parts of 2-acrylamide-2-methylpropanesulfonic acid, 1-1.6 parts of acrylic acid, 0.5-0.9 parts of sodium p-styrenesulfonate and 0.15-0.21 parts of modified phosphide, adding them into a beaker, adding 15-25 ml of deionized water for dissolution, adjusting the pH value, then adding 0.5-1.5 parts of dimethyldiallylammonium chloride, 3-3.8 parts of acrylamide and 0.02-0.08 parts of initiator, stirring evenly to completely dissolve all monomers, passing nitrogen for 5-15 minutes, placing in a constant temperature water bath at 45-55° C., reacting for 4-8 hours, washing with anhydrous ethanol and then shearing and granulating.

4. The low temperature resistant and crack resistant concrete according to claim 3, characterized in that: The modified phosphide comprises the following raw materials: 1-3g of triaminomethylphosphine oxide, 1-2g of hexachlorocyclotriphosphazene, 0.5-1.5g of melamine, 35-65ml of N,N-dimethylformamide, and 2-8ml of triethylamine.

5. The low temperature resistant and crack resistant concrete according to claim 4, characterized in that: The preparation method of the modified phosphide comprises the following steps: weighing 1-3g of triaminomethylphosphine oxide, dispersing the mixture in 15-25ml of N,N-dimethylformamide, and placing the mixture in an ice bath for stirring; weighing 1-2g of hexachlorocyclotriphosphazene, adding the mixture into a beaker, ultrasonically dispersing the mixture with 5-15ml of N,N-dimethylformamide, and then dropwise adding the mixture into the triaminomethylphosphine oxide dispersion; and continuing to react for 25-35min after the dropwise addition is completed; weighing 0.5-1.5g of melamine, adding the mixture into a beaker, ultrasonically dispersing the mixture with 15-25ml of N,N-dimethylformamide, and then dropwise adding the mixture into the dispersion; and continuing to react for 25-35min after the dropwise addition is completed. The uniformly stirred dispersion is poured into a high-pressure reactor, reacted at 100-140°C for 24-28h, and then centrifuged at a high speed. The product is then dried at 75-85°C for 2-8h and ground into powder.

6. The low temperature resistant and crack resistant concrete according to claim 5, characterized in that: The preparation method of the modified hydrotalcite is as follows: 2.1-2.9 parts of hydrotalcite and 0.4-0.8 parts of vinyl prepolymer are weighed and mixed evenly, dried in an oven at 75-85° C. for 6-10 hours, extruded and granulated at 210-250° C. on an extruder, and injection molded.

7. The low temperature resistant and crack resistant concrete according to claim 6, characterized in that: The preparation method of the modified polyurethane is as follows: 1.3-1.7 parts of modified hydrotalcite are added into 4-8 parts of polyurethane and stirred evenly, and then the mixture is put into a high-speed shearing machine for shearing treatment.

8. The method for preparing low temperature resistant and crack resistant concrete according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: weighing 95-105 parts of mineral materials, placing the mineral materials at 20-30°C, and mixing the mineral materials with 3-9 parts of modified polyurethane to uniformly stir the mixture.

Citation Information

Patent Citations

  • Flame-retardant environment-friendly polyurethane material and preparation method thereof

    CN111548476A

  • Anti-corrosion composite cement and preparation process thereof

    CN111892341A

  • Low-temperature-resistant polyurethane elastic concrete and preparation method thereof

    CN116751014A

  • Process for preparing water polyurethane / hydrotalcite composite paint with anti-ultraviolet property

    CN1715349A